Effects of firefighting on semen parameters: an exploratory study. Issue 1 (March 2021) - Engelsman, Michelle; Toms, Leisa-Maree L; Wang, Xianyu; Banks, Andrew P W; Blake, Debbie
Lay summary: Firefighters are occupationally exposed to heat intensities and chemical concentrations that may affect fertility. Twenty firefighters participated in an exploratory study assessing fertility of firefighters via an online survey and semen analysis. Data analysis included consideration of demographic characteristics, reproductive history and occupational exposures. Overall, firefighter semen parameters were below World Health Organisation reference values designating fertility in men. Firefighters younger than 45 years had a higher incidence of abnormal semen parameters (42%) than those aged 45 years or greater (9%). Increased rank and higher levels of occupational and/or personal hygiene were associated with improved semen quality. Increased frequency of fire exposure was associated with a reduction in normal forms, volume, sperm concentration and total sperm count. Sperm clumping was greater than 10% in 26% of samples, suggesting reduced semen quality. This exploratory study provides novel data that support the hypothesis of an association between semen quality and firefighter's occupational exposure to toxic environments.